The Influence of the Core Learning Model (Connecting, Organizing, Reflecting, Extending) on Critical Thinking Ability in Class X Geography Subjects in Man 1 Palu City - Anta Nurrahmah, Dwi; Nisa, Zumrotin; Khairurraziq; Nurvita (LPPM Universitas Tadulako, 2021)
The aim of this research is to determine the effect of CORE (Connecting, Organizing, Reflecting, Extending) learning on critical thinking skills in Geography Subjects. This type of research is quantitative with experimental methods. The quasi-experimental method is a scientific investigation that requires the researcher to manipulate and control one or more and observe the dependent variable, to see differences in accordance with the manipulation of the independent variables. The research design that will be used is a nonquivalent control group design, where this research uses a pretest and posttest carried out in both the experimental class and the control class. The results of the research show that there is a significant influence of the CORE (Connecting, Organizing, Reflecting, Extending) Learning Model on critical thinking skills in Class X Geography Subjects at MAN 1 Palu City. This is proven by the results of the t-test using the independent sample t-test formula. The results show a significance value (2-tailed) of 0.007 < 0.05 so Ho is rejected and Ha is accepted. Class X students' critical thinking skills regarding geography learning using the CORE learning method.